Nilai Tambah Modal Manusia dan Keberlangsungan Bisnis Perusahaan Sektor Consumer Non-Cyclicals - Asri Khayati; Roro Diyah Puspita Sari; Axel Giovanni (Universitas Muhammadiyah Magelang, 2022)
The world economic recession caused by the Covid-19 Pandemic distracted companies from maintaining business continuity, the consumer goods sector index declined in the first quarter of 2020 to reach its lowest level since 2013. Business continuity is defined as the company's capability to align its resources to increase opportunities growth and prospects in the future, business continuity has a strategic role in supporting the long-term value creation of the company. This study aims to provide empirical evidence regarding aspects of business continuity in the value-added perspective of human capital. The sample used in this study were 49 companies that are members of the non-cyclicals consumer sector for the 2016-2020 period. The analytical tool used in this research is simple linear regression. The results of this study indicate that the added value of human capital can improve aspects of the company's business continuity.